2005
DOI: 10.1002/aoc.1007
|View full text |Cite
|
Sign up to set email alerts
|

On‐line photodecomposition for the determination of antimony species

Abstract: On-line UV photooxidation by peroxodisulfate was coupled to ion chromatography hydride generation atomic fluorescence spectroscopy (IC-UV-HG-AFS) for the speciation of inorganic antimony [Sb(III) and Sb(V)] and methylated species. Several parameters (UV lamp, irradiation time and peroxodisulfate concentration) that greatly influence the sensitivity of these three antimony species were investigated in depth. Under optimized conditions, photodecomposition resulted in an improvement in methylantimony species sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It has been shown that Sb (III) is easily oxidized to Sb (V) within a short time at low concentrations (Filella, Belzile & Chen, 2002b;Miravet, López-Sánchez & Rubio, 2004;Miravet, Bonilla, López-Sánchez & Rubio, 2006b). …”
Section: Migration Studymentioning
confidence: 99%
“…It has been shown that Sb (III) is easily oxidized to Sb (V) within a short time at low concentrations (Filella, Belzile & Chen, 2002b;Miravet, López-Sánchez & Rubio, 2004;Miravet, Bonilla, López-Sánchez & Rubio, 2006b). …”
Section: Migration Studymentioning
confidence: 99%
“…118 The optimization of the irradiation time and addition of K 2 S 2 O 8 solution result in a detection limit for Me 3 Sb similar to that for inorganic species: 0.03, 0.04, and 0.03 mg L À1 for Sb(III), Sb(V) and Me 3 Sb, respectively. 119 The main applications of Sb speciation with AFS detection are summarised in Table 3.…”
Section: Speciation With Chromatographic Separationmentioning
confidence: 99%
“…After sample collection and return to the laboratory, samples of plant material are typically pre-processed immediately by ovendrying, 12,13 freeze-drying 14,15 or frozen un-treated 16 (Table 1). For other studies it is unclear exactly when freeze-drying took place.…”
Section: Sb-species Stability and Extraction From Solid Biological Ma...mentioning
confidence: 99%
“…4). 13 As seen from Fig. 4, one of the main problems associated with the identification of species by using HPLC is peak movement due to matrix effects introduced by the sample.…”
Section: Sb Speciation In Biological Matrices Based On Hplc Separationmentioning
confidence: 99%
See 1 more Smart Citation